PERILAKU MENYONTEK PADA REMAJA - Hartosujono & Nurul Komari Sari (LPPM Universitas Proklamasi 45, 2015)
Academic cheating is perceived as a common phenomenon, primarily in middle and high school levels. It is because academic achievement is more pursued in those two school levels. Objective of this preliminary research is to understand the reasons of academic cheating behavior. One high school student participates in this qualitative research. This research revealed that the subject is more likely to cheat because of external factor rather than internal factor. The external factor of cheating behavior is peer influence, whilst the internal factor is subject’s less confidence on his ability to accomplish the exam.